The Beginning of the Controversy About the Real Difference Between Essence and Existence: The Stance of Giles of Rome - Surzyn, Jacek (Folia Philosophica, 2000)
The present article shows the beginning of the controversy about the real difference between essence and existence. The controversy started with the declaration of Giles of Rome, who was the first to describe the difference between essence and existence as an inter rem et rem difference. In this way, he brought a bout a reification of essence and existence, which deviated completely from the views of Thomas Aquinas, for whom essence and existence form a compositum in a complex type of being, combining with each other according, to the principle of actuality and potentiality. Existence becomes thus an actualisation of essence, with the latter remaining towards the former in the relation of potentiality. Later, a very acute controversy erupted over the problem of the real difference in which its advocates often cited the views of Giles of Rome.